Immunoglobulin G subclass responses of children during infection with Onchocerca volvulus. - Gbakima, A A (1996)
To characterize the patterns of immunoglobulin G (IgG) subclass and IgE reactivity during the early stages of onchocerciasis, sera were collected from 224 children (age groups, 2 to 5, 6 to 10, and 11 to 15 years) residing in a region of Sierra Leone where Onchocerca volvulus is endemic, and these samples were tested by enzyme-linked immunosorbent assay for their reactivity to adult antigens (OvAg) and against four recombinant proteins (OV11, OV27, OV29, and OV16). Over 88% of the samples contained detectable levels of anti-OvAg IgG. In samples from microfilaria (MF)-positive children, IgG4 responses were significantly elevated and constituted on average 39, 35 and 28% of the total IgG responses for the age groups of 2 to 5, 6 to 10, and 11 to 15 years, respectively. For MF-negative individuals, the mean contributions of IgG4 to the total IgG response were 11% (2 to 5 years), 27% (6 to 10 years), and 56% (11 to 15 years). OvAg-specific IgE was detectable in the sera from both MF-negative and MF-positive individuals. To increase the specificity of the response, recombinant antigens OV11, OV27, and OV29 were tested individually or as a cocktail. Nearly 50% of the MF-negative children and 85% of the MF-positive children had detectable levels of IgG against at least one of the recombinant antigens. Only a small portion of the IgG against the recombinant peptides was IgG4. The prevalence of IgG against OV16 in samples from MF-negative children was 51%, and that for MF-positive children was 75%. The general profile of the humoral immune responses mounted by both MF-positive and a large percentage of the MF-negative children during the initial phases of infection with O. volvulus is similar to the profile reported for adults harboring chronic O. volvulus infections. These results suggest that very quickly after infection, the interactions between parasite and host result in an immunological environment that may contribute to the maintenance of a long-term, chronic infection.